An open source hp-adaptive discontinuous Galerkin finite element solver for linear elasticity. (September 2022) - Wiltshire, Thomas; Bird, Robert E.; Coombs, William M.; Giani, Stefano
Highlights: High accuracy discontinuous Galerkin finite element code. Automatic hp-adaptivity. The code is easy to modify to solver other physical equations. Easy to use Matlab code. Abstract: Open source codes are a key ingredient to greater research integrity and accountability in computational science and engineering. However, many of these codes have not been developed with modification of the base code as their primary consideration. Existing codes may provide an environment for researchers to quickly test out their ideas under different physical conditions in a high level way but they are not always ideal for those interested in the development of numerical methods. The majority of existing open source discontinuous Galerkin finite element codes are written in C++ and there is a significant learning curve for junior researchers to adopt, understand and modify the underlying code/routines. This paper presents an open source h p -adaptive discontinuous Galerkin finite element code written in MATLAB that has been explicitly designed to make it easy for users, especially MSc/PhD-level researchers, to understand the method and implement new ideas within the core code. Although the code is focused on solving problems in linear elasticity, it is straightforward to modify it to solve other physical equations.